Applying Make a Match Model to Improve Students Outcomes in Language Learning - Idham, Idham (Journal of English Language and Education, 2026)
This study aims to improve the learning outcomes of Grade VII students at SMP Negeri 03 Baras on pantun (traditional Malay poetry) material through the implementation of the make a match learning model. The study was motivated by the low cognitive absorption among students, attributed to several factors, including inadequate instructional content delivery and the use of inappropriate learning models. This classroom action research (CAR) was conducted over two cycles. Cycle I was implemented on May 17, 2023, while Cycle II was carried out on June 7, 2023. The pre-cycle results indicated that the classical learning mastery rate reached only 38.10%. In Cycle I, an improvement was observed, with the classical learning mastery rate rising to 50.00%. In Cycle II, student learning outcomes further improved to 78.57%. These findings demonstrate that the make a match learning model, when applied to Indonesian Language instruction—particularly in the context of pantun material—is effective in enhancing student learning outcomes, enabling students to complete tasks more readily through collaborative group work.